Oxidative Peptide Cleavage and Decarboxylation by the MPO-H(2)O(2)-Cl(−) Antimicrobial System - Selvaraj, Ratnam J. (1974)
The antimicrobial activities of the myeloperoxidase-H(2)O(2)-halide system have received considerable attention recently. The precise mechanism by which this system exerts its lethal activity is presently not clear. In an effort to learn more regarding a possible mechanism of action, the susceptibility of protein-bound amino acids to enzymatic attack by myeloperoxidase (MPO) in the presence of chloride ions was investigated. [1, 7-(14)C]diaminopimelic acid (DAP) was incorporated into Escherichia coli W-7 proteins with little randomization of the radioactivity. Under appropriate conditions, it was observed that the MPO-H(2)O(2)-halide system released approximately 94% of the radioactivity from labeled bacteria. This would indicate that, in addition to decarboxylation, peptide bonds are also split during this reaction. The oxidative decarboxylation of DAP-labeled bacteria by MPO (i) is Cl(−) dependent, (ii) has an acid pH optimum, (iii) requires a specific concentration of H(2)O(2) for activity, (iv) reaches a plateau by 25 min, and (v) is markedly inhibited by taurine. These properties are similar to those observed with free amino acids. It appears from these data that MPO can not only decarboxylate free and bound amino acids, yielding aldehydes, but also it can actively participate in oxidative peptide cleavage. Both of those activities may play a critical role in the microbicidal action of the leukocyte.